Including LGBTQ parented families in schools : research to inform policy and practice - Mann, Trent; Jones, Tiffany (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores the experiences of LGBTQ+ parented families in school communities and provides a voice for this overlooked group who are becoming an increasingly common form of family diversity in school communities. Approaching the topic from a strength-based psychological perspective, the book presents LGBTQ+ parents' suggestions for school improvements and supportive structures and provides empirical evidence to inform future LGBTQ+ inclusive educational policy. Research based yet practically focused, it will be a valuable resource for researchers, students, and education professionals alike"--
"Routledge focus"--from cover.
Keywords: Children of sexual minority parents -- Education; Sexual minority parents; Parent-teacher relationships; Inclusive education; Sexual minorities' families; Home and school; Education and state; Homosexuality and education; Sexual minorities -- Education; EDUCATION / Parent Participation